Flexible-detachable dual-output sensors of fluid temperature and dynamics based on structural design of thermoelectric materials. (August 2018) - Seo, Byungseok; Hwang, Hayoung; Kang, Sunggu; Cha, Youngsun; Choi, Wonjoon
Abstract: Multifunctionalities with self-powered capability are crucial for miniaturized, scattered devices to sense temperature and dynamics of fluids, which are intrinsic parameters to monitor environmental or industrial features. Herein, we present flexible-detachable dual-output fluid sensors employing the structural design of thermoelectric materials (SDTMs) that are artificially patterned TMs. The SDTMs enable the successive thermoelectric waves as the raw voltage signals with two distinct peaks that can reflect fluid temperature and dynamics, in contact with working fluids. The 1st-peak voltage provides the precise sensing of fluid temperature, while the duration between 1st- and 2nd-peaks indicates the moving velocity. A flexible-detachable SDTM-based sensor comprising of pre-designed Bi2 Te3 pattern between cellulose and PET substrates performs high-resolution sensing of temperature and velocity (< 0.19 K and < 0.03 cm/s) and facilitates the sticker-like functions through high-reproducibility (> 93%) of sensing under transfers between flat and curved surfaces. Furthermore, a scalable sensor array (4-by-4 SDTMs array at 16 pixels) is developed as a large-area device for real-time detection of fluid temperature and dynamics at multiple positions, accompanying with self-power generation of 42 μW/cm 2 . The new methodology using SDTMs can contribute to developing next-generation sensors having advanced features, such as multi-detection and diversely integrated flexible-detachable functions. Graphical abstract: Structural design of thermoelectric materials (SDTMs) that are artificially patterned TMs array enables successive thermoelectric waves producing the voltage signals that can reflect the fluid temperature and moving dynamics as a flexible-detachable dual-output sensor. fx1 Highlights: Flexible-detachable dual-output fluid sensors using structural design of thermoelectric materials (SDTMs) were developed. SDTMs are artificially patterned TMs to produce successive thermoelectric waves (TWs) with two distinct peaks. First peak and duration between two peaks in voltage signals from TWs reflect fluid temperature and dynamics. Flexible SDTM sensors comprising of Bi2 Te3 patterns perform high-resolution sensing of fluid temperature and velocity. Sensor array (4-by-4 SDTMs at 16 pixels) enabled large-area sensing at multiple positions with self-power generation.